Tanggung Jawab Notaris Dalam Penyimpanan Akta In Originali Sebagai Minuta Akta - Utari Dewi, Theresia Gst Agung Indah; Martana, Nyoman (Acta Comitas, 2020)
The purpose behind this paper is to understand the implementation in practice related to depositing the deed in originali as a minuta deed at the Notary's office and the responsibility of the notary related to the deposit of the deed in originali as a deed minuta. The method to researching this problem is using empirical juridicial. This research uses an approach in law that is an approach using a statutory regulation (The Statue Approach) and an approach by looking at the facts that occur in the field (The Fact Approach). There are two supporting data which is Interviews data as primary data and literature, laws , and books as Secondary data. Qualitative descriptive analysis technique used in this study as a analysis technique. Compiling data collected systematically after all data has been collected both of them. The results of the discussion obtained show that (1) Implementation in practice of depositing the deed in originali as a minuta deed at the Notary Office is wrong, for example, the deed of Power of Attorney Imposing Mortgage Rights (SKMHT). SKMHT made by Notary / PPAT in practice is made all original in originali in two copies. One deed in originali is kept as part of a collection of Notary protocols as minuta, another deed in originali is given to the authorized person. The purpose of keeping the deed in originali as a minuta is as an archive or document by a Notary Public, in addition to that in binding the deed minuta bundle, the numbers of the minuta deactivate sequentially. (2) Notaries are still responsible for keeping the deed in originali as a minuta deed, because it is a State document, so it is obligatory for each Notary to maintain and store it in a good place, so that it is not easily damaged, disappeared or lost. Tujuan dalam penulisan ini adalah untuk mengetahui dan menganlisis mengenai implementasi terkait penyimpanan akta in originali sebagai minuta akta di kantor Notaris dan tanggung jawab oleh notaris terkait disimpannya akta in originali sebagai minuta akta. Jenis penelitian yuridis empiris sebagai metode dalam permasalahan penelitian ini. Data primer bersumber dari wawancara dan data sekunder bersumber dari literature, buku-buku, maupun undang-undang. Teknik analisis yang digunakan dalam penelitian ini ialah teknik kualitatif Kesimpulan yang diperoleh menunjukkan bahwa (1) Pelaksanaan dalam praktek terhadap penyimpanan akta in originali sebagai minuta akta di kantor Notaris salah contohnya akta Surat Kuasa Membebankan Hak Tanggungan (SKMHT). SKMHT yang dibuat oleh Notaris/PPAT dalam prakteknya tersebut dibuat semuanya asli in originali dalam dua rangkap. Satu lembar akta in originali disimpan sebagai bagian dari kumpulan protokol Notaris sebagai minuta, satu lembar akta in originali lagi diberikan kepada penerima kuasa.  (2) Notaris tetap bertanggungjawab terhadap penyimpanan akta in originali sebagai minuta akta, karena merupakan dokumen Negara sehingga wajib oleh setiap Notaris memelihara dan menyimpan ditempat yang baik, agar tidak mudah rusak, lenyap ataupun hilang.